PENGEMBANGAN MODEL PERAN ORANG TUA, GURU, DAN MASYARAKAT DALAM PROSES PEMBELAJARAN UNTUK MEMBENTUK INTENSI BERPERILAKU ANAK PEDULI LINGKUNGAN - Maratun Nafiah; Sri Kawuryan Hastawati (Pendidikan Fisika FKIP UNEJ, 2016)
Nowadays, Indonesia faces many environmental problems. These problems happen due to much global warming issue. Consequently, it is necessary to do learning process continuously so that the students care about environment leading to their habits. Through teaching learning process, the sudents will have sensitivity, evaluating competences, and decision making competences suitable with environmental problems faced. Based on this situation, this research is aimed to identify parents’, school, and society roles in learning process to shape behaviour intention of the students caring of environment. Data was collected through Focus Group Discussion and questionnaires distributed. The results of instruments field trial test with 50 respondents from 52 items is that 4 items were dropped and 48 items were valid with reliability coefficient reached 0.91. Descriptive statistics used to analyze data are mean for all respondents as many as 600 students counted by determining on items less than 3.0 (found as many as 6 items). Research findings are recommended to stakeholeders used to make a policy about learning process in shaping behaviour intention of environmental caring students. Kata Kunci: parents’ roles, school roles, society roles, learning process, behaviour intention, caring of environment